Reliability and feasibility of change of direction testing in national basketball players - Faulks, T.; Petway, A.; Drury, M.; Walter, S. (Journal of Human Kinetics, 2025)
The reliability and feasibility of a 2-2 shuffle test time against on-court lateral change of direction performance was examined. Ten male national league players performed two trials of the 2-2 shuffle test per direction and were compared against their total steals throughout the season. Intraday reliability of the test was computed using Bland-Altman plots, intraclass correlation coefficients (ICCs) and coefficients of variations (CVs). Anthropometric and total steals differences between fast and slow 2-2 shuffle performance were assessed with an independent t-test, percent difference (Diff %), and effect size (ES). The 2-2 shuffle test time for dominant (ICC = 0.86, CV = 8.61%) and non-dominant (ICC = 0.90, CV = 9.30%) directions met pre-determined reliability thresholds (ICC > 0.8, CV < 10%). Faster 2-2 shufflers were significantly shorter (1.91 ± 0.03 vs. 2.02 ± 0.09, Diff % -5.45, p = 0.03, ES = -1.3) in height and accrued more total steals than their slower counterparts (15.60 ± 9.24 vs. 9.00 ± 6.44, Diff % 42.31, p = 0.22, ES = -0.8). Practitioners may add the 2-2 shuffle to their assessment battery as the test time is a reliable metric and can show the direction for on-court lateral performance as reflected by total steals.